IMPROVEMENT OF PHONOLOGICAL SKILLS – IMPROVEMENT OF READING - Tubele, Sarmite; Serova, Kristine (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article “Improvement of Phonological Skills – Improvement of Reading” underlines the importance of phonological awareness in the development of reading skills. Several studies show that reading is a very complex skill that involves cognitive processes, intellect and other variables, but the key factor for the development of good reading skills is a good level of phonological awareness.Before the intervention a special material was created, which was systematically ordered according to the current level of each child’s phonological awareness abilities. Children were evaluated before and after the intervention.The aim of this research is to evaluate the possibility to develop good phonological analysis and synthesis skills for six to seven years old children with phonematic perception disorder.The research methods used in the study are the analysis of scientific literature, the gathering of primary data with specially designed evaluation material, the analysis of gathered primary data, and the observation of child’s performance during the training sessions.